THE IMPORTANCE OF ADHERENCE TO THE CHILD HEALTH REGISTER IN MONITORING CHILD DEVELOPMENT: AN INTEGRATIVE REVIEW (CIPEEX, 2025)
Introduction: The Child Health Record is an essential tool for comprehensively monitoring child growth and development, as it gathers information on weight, height, neuropsychomotor development, and vaccination history. Its proper use contributes to continuity of care, clinical decision-making, and epidemiological surveillance, strengthening primary health care. Objective: This study aims to identify the importance of adherence to the Child Health Record in monitoring child development. Methodology: This is an integrative literature review conducted in the Virtual Health Library (VHL) and PubMed databases. The descriptors "Child health," "Vaccination schedule," and "Child development" were used, combined with Boolean operators. Articles published between 2019 and 2024, in Portuguese and English, that directly addressed the topic were included. The search yielded 208 articles, of which 6 comprised the final sample after applying the inclusion and exclusion criteria. Results: The results indicated a significant decline in vaccination coverage among children and adolescents over the last ten years (2015-2025), linked to reduced health investment in developing countries and the spread of false information about vaccines, which intensified during the COVID-19 pandemic. In 2023, approximately 17 million children remained without any vaccine dose, contributing to the reemergence of previously controlled diseases, such as measles and polio. Furthermore, low adherence to the Child Health Record compromises both vaccination monitoring and the overall assessment of child development. Conclusion: It is concluded that adherence to the Booklet is essential for the promotion of child health and the effectiveness of public immunization policies.